Johann Christoph Gottscheds Briefwechsel - Historisch-kritische Ausgabe Band 8: November 1741 - Oktober 1742 - Gottsched, Johann Christoph (Briefwechsel, 2014)
Gottsched spent several months in Dresden while representing Leipzig University at Saxony's parliament. His correspondence lends insight to the events unfolding there and documents his interactions with his circle of acquaintances in Leipzig, whom he normally saw in person. Major topics in the correspondence include the theater, the War of Austrian Succession, and disagreements with Gottsched's critics Bodmer and Breitinger in Zurich.